Just another hydronephrosis? - Pradhan, Sumita; Shrestha, S; Shrestha, P; Verma, R (Journal of General Practice and Emergency Medicine of Nepal, 2011)
Obstruction at the upper end of ureter is one of the most common surgical problems that we face in day to day life. Diagnosis of hydronephrosis due to PUJ obstruction is not difficult either. But sometimes unrecognized obstruction can lead to many problems resulting in significant morbidity and sometimes even death. Giant hydronephrosis is a rare entity and giant pyonephrosis even rarer. Here we present a case of 19 year old male who presented with abdominal distension, shortness of breath and other gastrointestinal symptoms.